(untitled) (Indonesian Journal of Agrarian Law, 2026)
Land ownership disputes in Indonesia remain complex, particularly when conflicts arise between long-standing factual land control and formal legal ownership evidenced by certificates, reflecting a tension between legal certainty and substantive justice within agrarian law. This study analyzes the juridical aspects of unlawful acts in land tenure disputes through Decision Number 7/Pdt.G/2024/PN Pkl, using a normative juridical method with empirical reinforcement, combining statutory, conceptual, and case approaches, supported by limited interviews. The findings reveal that courts tend to prioritize formal legality, especially land certificates, as the primary basis for determining ownership, resulting in the rejection of claims based solely on factual control without formal evidence. Furthermore, the analysis shows that the elements of unlawful acts are closely linked to the validity of land rights, positioning legal ownership as a decisive factor in judicial reasoning. This condition illustrates an imbalance in the application of agrarian law, where legal certainty is upheld, yet substantive justice for parties with historical control over land is not always achieved. The study contributes to the development of agrarian law by emphasizing the need for a more balanced and inclusive approach that recognizes both formal legality and factual realities in land tenure. In this regard, improving access to land registration and strengthening mechanisms for legal recognition of long-term land control are essential steps to minimize agrarian conflicts and create a more equitable legal system.